Collective action and farm efficiency of male- and female-headed farm households in Ghana - Arnold Missiame; Rexford Akrong; Grace Darko Appiah-Kubi (Cogent Social Sciences, 2023)
AbstractCollective action through farmer groups has been seen to be significantly beneficial to especially smallholder farmers in sub-Saharan Africa (SSA), in terms of competitiveness, credit access, capacity building, and market access. Thus, it has been promoted as a strategy for rural development. Despite the many benefits of collective action, there is very little to no empirical evidence of its impact on the farm efficiency of rural women. This paper sought to measure the impact of collective action through farmer-based organizations (FBOs) on the technical efficiency (TE) of smallholder farmers using the stochastic frontier model and the inverse probability weighting estimator (IPW). Using representative data from 300 randomly selected smallholder cassava farmers in the Eastern region of Ghana we found that the age of the household head, years of experience in cultivation, size of the household, and the geographical location of the farm, independently have a significant influence on farmers’ decision to join FBOs. The results show that female farmers who belong to FBOs, on average, can produce about 63.5% of their potential yield while male members achieve only 57.8% of their potential yield, on average. The results further reveal that female farmers benefit the most from FBOs with their membership resulting in a 12% increase in their TE. The findings provide implications for the design of policies to improve women’s farm efficiency.